2000
DOI: 10.1046/j.1440-1746.2000.02045.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antibody responses against rectal mucosa‐associated bacterial flora in patients with ulcerative colitis

Abstract: These results suggest that B. vulgatus and a specific antibody response directed against it may play an important role in the pathogenesis of UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
3
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 30 publications
(39 reference statements)
5
80
3
3
Order By: Relevance
“…While there has been revived interest in intestinal microbes as contributing factors in IBD pathogenesis, studies have focused on endogenous commensal flora rather than on specific pathogens (e.g., Shigella, hemorrhagic E. coli, Salmonella, Amebiasis, Gonorrhea, Chlamydia, Clostridium difficle). A recent study reported the presence of Bacteroides vulgatus in the colonic mucosa of some UC patients (21). Our own study revealed another species of commensal bacteria, Fusobacterium varium, in the inflamed mucosa in UC patients (22).…”
Section: Bacterial Agents In Ulcerative Colitissupporting
confidence: 54%
“…While there has been revived interest in intestinal microbes as contributing factors in IBD pathogenesis, studies have focused on endogenous commensal flora rather than on specific pathogens (e.g., Shigella, hemorrhagic E. coli, Salmonella, Amebiasis, Gonorrhea, Chlamydia, Clostridium difficle). A recent study reported the presence of Bacteroides vulgatus in the colonic mucosa of some UC patients (21). Our own study revealed another species of commensal bacteria, Fusobacterium varium, in the inflamed mucosa in UC patients (22).…”
Section: Bacterial Agents In Ulcerative Colitissupporting
confidence: 54%
“…У хворих на ВК виявлена велика кількість антитіл до Bacteroides vulgatus, B. fragilis та Clostridium ramosum [70]. Білок із молекулярною масою 26 кДа, виді-лений з мембрани B. vulgatus, спричиняє утворення IgG у 54% хворих на ВК та 9% здорових людей.…”
Section: вступunclassified
“…У хворих на ВК домінували Bacteroides thetaiotaomicron. Встановлено, що на поверхні слизової кишечника пере-важають приблизно 69% бактероїдів (зокрема B. vulgatus), порівняно з іншими мік-роорганізмами [70,82].…”
Section: бактерії слизової оболонки товстого кишечникаunclassified
“…Recent reports have indicated that bacteria play an important role in the pathogenesis of mucosal inflammation in patients with ulcerative colitis (16,17). In addition, previous studies have shown that Fusobacterium varium bacteria are present in a significant number of patients with active ulcerative colitis, indicating that Fusobacterium varium is an elusive pathogenic factor involved in the pathogenesis of ulcerative colitis (16).…”
mentioning
confidence: 99%
“…In addition, previous studies have shown that Fusobacterium varium bacteria are present in a significant number of patients with active ulcerative colitis, indicating that Fusobacterium varium is an elusive pathogenic factor involved in the pathogenesis of ulcerative colitis (16). Another report suggested that the mucosa-associated microflora, especially that involving the Bacteroides species, plays an important role in the etiology of ulcerative colitis (17). Furthermore, several previous studies have suggested that resident enteric bacteria are necessary for the development of spontaneous colitis in animal experiments (18,19).…”
mentioning
confidence: 99%